Landasan Pengembangan Ilmu Pengetahuan di Dunia Muslim: Studi Kritik Hadis - Muhammad Thoriq; Mila Irmawati; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the primacy of science. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the primacy of science in the history of Ahmad No. 7965. The results and discussion of this study indicate that the status of the hadith has the quality of hasan li ghairihi with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 7965 is relevant to be used as a motivational basis for the development of knowledge in the Islamic world.